A silicon-oxygen negative electrode material containing an artificial SEI film and its preparation method and application
By forming an artificial SEI film on the surface of the silicon oxygen negative electrode material, the problem of instability of the SEI film of the traditional silicon oxygen negative electrode material is solved, which significantly improves the circulation performance and life, and reduces the battery production cost.
Patent Information
- Application Number
- CN202510239556.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the circulation process, traditional silicon oxygen negative electrode materials cause unstable, cracked and reconstructed SEI films, which consume a large amount of electrolyte, affecting the circulation performance of the battery.
By directed designing the mutual bonding between the binder and the conductive agent, using the self-match between functional groups, an artificial SEI film is formed on the surface of the silicon oxygen negative electrode to protect the modification to improve stability.
The formed artificial SEI film layer improves the mechanical stability and rate performance of the silicon oxygen negative electrode material, extends the cycle life, and reduces the cost of battery production.
Smart Images

Figure CN119742359A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a silicon-oxygen negative electrode material containing an artificial SEI film, and a preparation method and application thereof. Background Art
[0002] With the rapid development of 3C products and new energy vehicles, the development of lithium-ion batteries with high energy density, long battery life, and fast charging has become an urgent problem for researchers. The capacity of traditional negative electrode graphite (372mAh / g) is close to the theoretical limit, which limits the further improvement of the overall energy density of lithium-ion batteries. In this context, silicon-based negative electrodes are considered to be the most promising next-generation commercial negative electrode materials due to their superior theoretical specific capacity (4200mAh / g) and extremely high reserves (ranked second in the earth's crust).
[0003] Traditional silicon-oxygen anode has great potential, but it will cause great volume changes and unstable solid electrolyte interface (SEI) during the cycle. The unstable SEI film cannot withstand the huge volume changes of silicon during the electrochemical cycle, resulting in continuous rupture and reconstruction of the SEI film, consuming a large amount of electrolyte and affecting the cycle performance of the battery. Therefore, improving the mechanical properties of the SEI film is an important way to improve the stability of the SEI film, and it is also the key to the development of long-cycle lithium-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a silicon-oxygen negative electrode material containing an artificial SEI film, and a preparation method and application thereof. By directional design of the mutual bonding between a binder and a conductive agent and utilizing the self-matching between functional groups, a layer of artificial SEI film is formed on the surface of the silicon-oxygen negative electrode, and the surface of the silicon-oxygen negative electrode is protected and modified to solve the problems of poor uniformity and instability of the SEI film of the silicon-oxygen negative electrode material mentioned in the background technology, and to improve the cycle performance of the silicon-oxygen negative electrode material.
[0005] To achieve the above-mentioned purpose, the present invention provides a silicon-oxygen negative electrode material containing an artificial SEI film, wherein the silicon-oxygen negative electrode material is a core-shell structure, the material particle diameter is 5~8 μm, and it is composed of a silicon-oxygen negative electrode core and an artificial SEI film layer coated on the surface of the silicon-oxygen negative electrode core; the artificial SEI film includes a conductive agent and a binder; wherein the mass ratio of the silicon-oxygen negative electrode core, the binder and the conductive agent is 5: (0.05~0.25): (0.0005~0.003).
[0006] The present invention also provides a method for preparing the above-mentioned silicon-oxygen negative electrode material containing an artificial SEI film, comprising the following steps: S1, putting the ball-milled silicon dioxide into a CVD rotary kiln, introducing a gaseous carbon source for vapor deposition carbon coating, and then calcining at a high temperature under an inert atmosphere to obtain a silicon-oxygen negative electrode core; S2, mixing the silicon-oxygen negative electrode core, the binder and the deionized water in step S1, stirring them evenly by heating in a water bath, and then ultrasonically dispersing them to obtain a solution containing the binder uniformly coated on the surface of the silicon-oxygen negative electrode core; S3, modifying the conductive agent with a binder to obtain a conductive agent solution with good dispersibility; S4, mixing the conductive agent solution prepared in S3 with the solution prepared in S2 to obtain a slurry containing a conductive agent and a binder to cover the surface of the silicon-oxygen negative electrode core; S5, drying, molding and fusing the slurry prepared in S4 to obtain a granular powder containing a conductive agent and a binder co-coated on the surface of the silicon-oxygen negative electrode; S6. The material powder treated in S5 is subjected to high-temperature carbonization in an inert atmosphere to complete the coating of the surface of the silicon-oxygen negative electrode core by the artificial SEI film layer, thereby obtaining a silicon-oxygen negative electrode material containing an artificial SEI film.
[0007] Preferably, in S1, the gaseous carbon source is one or more of methane, ethane, acetylene, and propylene; the inert atmosphere is one or more of nitrogen or argon, wherein the gas flow ratio of the gaseous carbon source to the inert atmosphere is 1:2.
[0008] Preferably, in S1, the temperature of vapor deposition is 800-1000°C, and the time of vapor deposition is 2-4 h; the temperature of high-temperature calcination is 800-1000°C, and the time of high-temperature calcination is 2-3 h.
[0009] Preferably, in S2, the binder is one or more of sodium carboxymethyl cellulose, sodium alginate, and polyacrylic acid; The water bath heating temperature is 40~60 ℃, and the water bath heating time is 30~60 min.
[0010] Preferably, in S3, the conductive agent is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, conductive carbon black, and graphene; The binder is one or more of sodium carboxymethyl cellulose, sodium alginate and polyacrylic acid.
[0011] Preferably, in S4, the solid content of the slurry is 8-10%.
[0012] Preferably, in S5, the drying temperature is 80-120°C; the fusion machine speed is 400-600 rpm, and the fusion time is 30-60 min.
[0013] Preferably, in S6, the high temperature carbonization temperature is 600-800°C, the heating rate is 5-10°C / min, the high temperature carbonization time is 2-3 h, and the inert atmosphere is one or both of nitrogen and argon.
[0014] The present invention also provides application of the above silicon-oxygen negative electrode material containing an artificial SEI film in a lithium ion battery.
[0015] The present invention provides a silicon-oxygen negative electrode material containing an artificial SEI film, a preparation method thereof and an application thereof, which has obvious beneficial effects compared with the prior art. A thin layer of binder and conductive agent is deposited on the surface of the silicon-oxygen negative electrode core through a water bath coating and high-temperature carbonization process, participating in or promoting the formation of a thin, dense and elastic artificial SEI film.
[0016] The artificial SEI film coating layer prepared by the present invention can not only provide the mechanical integrity of the internal connection network and buffer the volume expansion of silicon particles during the cycle, but also provide high electrical conductivity, which is beneficial to the improvement of the material rate performance.
[0017] The silicon-oxygen negative electrode material containing an artificial SEI film prepared by the present invention will not dissolve in an organic solvent, and can maintain its structural integrity during the electrode preparation process. The artificial SEI film layer deposited on the surface of the silicon-oxygen negative electrode core can reduce the specific surface area of the material to a certain extent, reduce the generation area of the SEI film, reduce the loss of active lithium ions, and is beneficial to the improvement of the material's cycle performance.
[0018] The silicon-oxygen negative electrode material containing an artificial SEI film prepared by the present invention can generate hydrogen bonds between the abundant hydroxyl and carboxyl groups on the surface of the conductive agent and the carboxyl or hydroxyl groups in the binder through hydrogen bonding to form interlocking chains, participate in or promote the formation of a thin, dense and elastic SEI film, and effectively inhibit the growth of lithium dendrites.
[0019] The silicon-oxygen negative electrode material containing an artificial SEI film prepared by the present invention can achieve uniform coating of the conductive agent on the surface of the silicon-oxygen negative electrode by controlling the mass ratio of the conductive agent to the binder. When the silicon-oxygen negative electrode material containing an artificial SEI film layer prepared by the present invention is used to make lithium batteries, the addition ratio of carbon nanotubes in the homogenization process can be effectively reduced, thereby saving a large amount of battery production costs.
[0020] In summary, the silicon-oxygen negative electrode material containing an artificial SEI film layer prepared by the preparation method of the present invention has good mechanical stability, good rate performance, and good cycle life. The preparation process is simple, the cost is low, and it is suitable for industrial production.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the silicon negative electrode composite material in Example 1 of the present invention.
[0023] Figure 2 This is a SEM image of the silicon negative electrode composite material in Example 2 of the present invention.
[0024] Figure 3 This is a SEM image of the silicon negative electrode composite material in Example 3 of the present invention.
[0025] Figure 4 This is a SEM image of the silicon negative electrode composite material in Example 4 of the present invention.
[0026] Figure 5 This is a SEM image of the silicon particle core in Comparative Example 1 of the present invention.
[0027] Figure 6 The figure is a comparison chart of the cycle performance of lithium batteries assembled with the lithium battery negative electrode materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1.
[0028] Figure 7 The peel strength test results of the silicon-oxygen negative electrode materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below by means of the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application and belong to the scope of protection of the present invention.
[0030] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0031] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0032] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.
[0033] Example 1 This embodiment provides a method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film, comprising the following steps: S1, silicon dioxide (SiO x ) was ball-milled into particles with a median particle size of 5 μm, transferred to a CVD furnace, introduced acetylene, and vapor-deposited at 900 °C for 4 h to complete carbon coating, obtaining SiO with a thin carbon layer. x Then take out 10 g of SiO x The powder was transferred to a tube furnace and calcined at 950 °C for 3 h in a nitrogen atmosphere to obtain the silicon-oxygen negative electrode core.
[0034] S2. Weigh 3.33 g of PAA gel (solid content is 6%) and place it in 80 g of deionized water. Stir it continuously in a 50 °C water bath for 30 min. After PAA and water are fully miscible, take 10 g of the silicon particle core in step S1 and add it to the solution. Continue heating and stirring in a 50 °C water bath for 2 h. Then, ultrasonically disperse the solution for 30 min to ensure that the silicon particle core is evenly suspended in the PAA gel, and obtain a solution in which PAA is evenly coated on the surface of the silicon oxygen negative electrode core.
[0035] S3. Weigh 0.75 g of single-walled carbon nanotubes and 1.67 g of PAA gel, dissolve them in 20 g of deionized water, and disperse them by ultrasonic for 1 h to evenly disperse the carbon nanotubes in the aqueous solution.
[0036] S4. Mix the uniformly dispersed carbon nanotube aqueous solution in S3 with the solution in S2, and mechanically stir at room temperature for 4 h to obtain a slurry containing carbon nanotubes and PAA co-coated on the surface of the silicon oxygen negative electrode core.
[0037] S5. The slurry in S4 is transferred to a forced air drying oven, dried overnight at 80°C to set the shape, and processed in a fusion machine to obtain a granular powder containing carbon nanotubes and PAA co-coated on the surface of the silicon-oxygen negative electrode.
[0038] S6. The dried powder in S5 was transferred to a vacuum tube furnace and carbonized at 800 °C for 2 h in a nitrogen atmosphere at a heating rate of 5 °C / min to obtain a silicon-oxygen negative electrode material containing an artificial SEI film.
[0039] Example 2 This embodiment provides a method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film, comprising the following steps: S1, silicon dioxide (SiO x ) was ball-milled into particles with a median particle size of 5 μm, transferred to a CVD furnace, introduced acetylene, and vapor-deposited at 900 °C for 4 h to complete carbon coating, obtaining SiO with a thin carbon layer. x Then take out 10 g of SiO x The powder was transferred to a tube furnace and calcined at 950 °C for 3 h in a nitrogen atmosphere to obtain the silicon-oxygen negative electrode core.
[0040] S2. Weigh 1 g of PAA gel (solid content of 20%) and place it in 80 g of deionized water. Stir continuously in a 50 °C water bath for 30 min. After PAA and water are fully miscible, take 10 g of the silicon particle core in step S1 and add it to the solution. Continue heating and stirring in a 50 °C water bath for 2 h. Then ultrasonically disperse the solution for 30 min to ensure that the silicon particle core is evenly suspended in the PAA gel, and obtain a solution in which PAA is evenly coated on the surface of the silicon oxygen negative electrode core.
[0041] S3. Weigh 0.75 g of single-walled carbon nanotubes and 0.5 g of PAA glue, dissolve them in 20 g of deionized water, and disperse them by ultrasonic for 1 h to evenly disperse the carbon nanotubes in the aqueous solution.
[0042] S4. Transfer the evenly dispersed carbon nanotube aqueous solution in S3 and mix it with the solution in S2, and stir it mechanically at room temperature for 4 hours to obtain a slurry containing carbon nanotubes and PAA co-coated on the surface of the silicon oxygen negative electrode core.
[0043] S5. The slurry in S4 is transferred to a forced air drying oven, dried overnight at 80°C to set the shape, and processed in a fusion machine to obtain a granular powder containing carbon nanotubes and PAA co-coated on the surface of the silicon-oxygen negative electrode.
[0044] S6. The dried powder in S5 was transferred to a vacuum tube furnace and carbonized at 800 °C for 2 h in a nitrogen atmosphere at a heating rate of 5 °C / min to obtain a silicon-oxygen negative electrode material containing an artificial SEI film.
[0045] Example 3 This embodiment provides a method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film, comprising the following steps: S1, silicon dioxide (SiO x ) was ball-milled into particles with a median particle size of 5 μm, transferred to a CVD furnace, introduced acetylene, and vapor-deposited at 900 °C for 4 h to complete carbon coating, obtaining SiO with a thin carbon layer. x Then take out 10 g of SiO xThe powder was transferred to a tube furnace and calcined at 950 °C for 3 h in a nitrogen atmosphere to obtain the silicon-oxygen negative electrode core.
[0046] S2. Weigh 3.31 g of PAA gel (solid content of 6.05%) and place it in 80 g of deionized water. Stir continuously in a 50 °C water bath for 30 min. After PAA and water are fully miscible, take 10 g of the silicon particle core in step S1 and add it to the solution. Continue heating and stirring in a 50 °C water bath for 2 h. Then ultrasonically disperse the solution for 30 min to ensure that the silicon particle core is evenly suspended in the PAA gel, and obtain a solution in which PAA is evenly coated on the surface of the silicon oxygen negative electrode core.
[0047] S3. Weigh 0.75 g of single-walled carbon nanotubes and 1.65 g of PAA glue, dissolve them in 20 g of deionized water, and disperse them by ultrasonic for 1 h to evenly disperse the carbon nanotubes in the aqueous solution.
[0048] S4. Mix the uniformly dispersed carbon nanotube aqueous solution in S3 with the solution in S2, and mechanically stir at room temperature for 4 h to obtain a slurry containing carbon nanotubes and PAA co-coated on the surface of the silicon oxygen negative electrode core.
[0049] S5. The slurry in S4 is transferred to a forced air drying oven, dried overnight at 80°C to set the shape, and processed in a fusion machine to obtain a granular powder containing carbon nanotubes and PAA co-coated on the surface of the silicon-oxygen negative electrode.
[0050] S6. The dried powder in S5 was transferred to a vacuum tube furnace and carbonized at 800 °C for 2 h in a nitrogen atmosphere at a heating rate of 5 °C / min to obtain a silicon-oxygen negative electrode material containing an artificial SEI film.
[0051] Example 4 This embodiment provides a method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film, comprising the following steps: S1, silicon dioxide (SiO x ) was ball-milled into particles with a median particle size of 5 μm, transferred to a CVD furnace, introduced acetylene, and vapor-deposited at 900 °C for 4 h to complete carbon coating, obtaining SiO with a thin carbon layer. x Then take out 10 g of SiO x The powder was transferred to a tube furnace and calcined at 950 °C for 3 h in a nitrogen atmosphere to obtain the silicon-oxygen negative electrode core.
[0052] S2. Weigh 3.32 g of PAA gel (solid content of 6.02%) and place it in 80 g of deionized water. Stir it continuously in a 50 °C water bath for 30 min. After PAA and water are fully miscible, take 10 g of the silicon particle core in step S1 and add it to the solution. Continue heating and stirring in a 50 °C water bath for 2 h. Then, ultrasonically disperse the solution for 30 min to ensure that the silicon particle core is evenly suspended in the PAA gel, so as to obtain a solution in which PAA is evenly coated on the surface of the silicon oxygen negative electrode core.
[0053] S3. Weigh 0.75 g of single-walled carbon nanotubes and 1.66 g of PAA glue, dissolve them in 20 g of deionized water, and disperse them by ultrasonic for 1 h to evenly disperse the carbon nanotubes in the aqueous solution.
[0054] S4. Mix the uniformly dispersed carbon nanotube aqueous solution in S3 with the solution in S2, and mechanically stir at room temperature for 4 h to obtain a slurry containing carbon nanotubes and PAA co-coated on the surface of the silicon oxygen negative electrode core.
[0055] S5. The slurry in S4 is transferred to a forced air drying oven, dried overnight at 80°C to set the shape, and processed in a fusion machine to obtain a granular powder containing carbon nanotubes and PAA co-coated on the surface of the silicon-oxygen negative electrode.
[0056] S6. The dried powder in S5 was transferred to a vacuum tube furnace and carbonized at 800 °C for 2 h in a nitrogen atmosphere at a heating rate of 5 °C / min to obtain a silicon-oxygen negative electrode material containing an artificial SEI film.
[0057] By comparing Examples 1 to 4, it can be seen that the types of PAA added in each Example are different, mainly reflected in the different PAA solid content values. The performance of the silicon negative electrode material containing the artificial SEI film prepared by PAA corresponding to different solid content values is also slightly different. Specific performance characterization tests include: SEM, peel strength, and cycle performance. Detailed results are shown in the attached figure of the specification.
[0058] Comparative Example 1 Silicon dioxide (SiO x ) was ball-milled into particles with a median particle size of 5 μm, transferred to a CVD furnace, and acetylene was introduced for vapor deposition carbon coating to obtain SiO with a thin carbon layer. x Then take out 10 g of SiO x The powder was transferred to a tube furnace and calcined at 950 °C for 3 h in a nitrogen atmosphere to obtain the silicon-oxygen negative electrode core.
[0059] The artificial SEI film-coated silicon negative electrode composite materials prepared in Examples 1 to 4 of the present invention and the silicon particle core negative electrode material prepared in Comparative Example 1 were observed by SEM. Figures 1 to 4As shown in Figure 2, the surface of the silicon composite negative electrode material coated with the artificial SEI film is obviously rough, and there are clearly visible traces of the interwoven network of carbon nanotubes. Figure 5 The surface of the core of the prepared silicon particles is relatively smooth. By comparison, it can be seen that the preparation method provided by the present invention can successfully achieve coating a layer of stable artificial SEI film on the surface of the silicon negative electrode.
[0060] The finished materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 were used to assemble button batteries of model 2032 for evaluation. The specific scheme was as follows: the prepared materials, conductive agent SP, binder CMC and SBR were mixed in a mass ratio of 80:10:3:7 to obtain a slurry, the slurry was evenly dispersed and then coated on a 9 μm copper foil to form a negative electrode sheet, a lithium sheet was used as a counter electrode, the prepared negative electrode sheet and a lithium metal sheet were assembled into a lithium ion button battery, and the capacity and cycle performance tests were performed.
[0061] Figure 6 The following is a comparison chart of the cycle performance of lithium batteries assembled from the lithium battery negative electrode materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1. Examples 1 to 4 are four different silicon-oxygen negative electrode materials coated with artificial SEI membranes, and the main difference lies in the type of coated binder; Comparative Example 1 is a silicon-oxygen negative electrode material without artificial SEI membrane coating. Figure 6 It can be seen that the cycle performance of silicon-oxygen negative electrode materials containing artificial SEI film is far superior to that of silicon-oxygen negative electrode materials without artificial SEI film coating. This is mainly attributed to the fact that the artificial SEI film layer can not only effectively isolate the corrosion of the electrolyte to the negative electrode and weaken the interfacial side reactions, but also effectively dissipate the stress caused by the volume expansion of the silicon negative electrode, significantly enhancing the structural stability of the silicon negative electrode, thereby greatly improving the cycle performance of silicon-oxygen negative electrode materials containing artificial SEI film.
[0062] Figure 7 The peel strength test results of the silicon-oxygen negative electrode materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are shown in FIG. Figure 7 It can be seen that the peeling forces of Examples 1 to 4 prepared from the silicon-oxygen negative electrode composite material coated with an artificial SEI film are all greater than the silicon particle core negative electrode material without an artificial SEI film in Comparative Example 1. The peeling strength is mainly reflected in the degree of close bonding between the silicon negative electrode active material, the conductive agent and the copper foil in the binder electrode structure. The greater the peeling force, the stronger the bond between the three, the less likely the active material will fall off the copper foil, and the more it can withstand changes in the volume of the active material. Therefore, the silicon composite negative electrode material coated with an artificial SEI film is more conducive to electrode stability, ensuring that the cycle life of the battery is greatly improved.
[0063] In summary, when the silicon composite negative electrode material coated with the artificial SEI film prepared in Examples 1 to 4 of the present invention is used as a negative electrode material for a lithium battery, it can attract the active material and the like to form a strong interfacial force, and an appropriate amount of carbon nanotubes can form an interwoven network structure, which has a strong interfacial force on SiO x The particles are encapsulated to avoid SiO x The particles break and lose electrical contact. The bonding between functional groups is used to realize the compounding of the silicon particle core and the artificial SEI film, avoiding the shedding of active silicon and contact with the electrolyte. The three-dimensional carbon nanotube conductive network not only ensures the overall conductivity of the silicon composite negative electrode material, but also buffers the volume expansion of the silicon negative electrode composite material, thereby improving the cycle stability of the silicon negative electrode.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A silicon-oxygen negative electrode material containing an artificial SEI film, characterized in that: The silicon-oxygen negative electrode material is a core-shell structure with a material particle diameter of 5-8 μm, and is composed of a silicon-oxygen negative electrode core and an artificial SEI film layer coated on the surface of the silicon-oxygen negative electrode core; the artificial SEI film includes a conductive agent and a binder; wherein the mass ratio of the silicon-oxygen negative electrode core, the binder and the conductive agent is 5: (0.05-0.25): (0.0005-0.003).
2. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 1, characterized in that: The following steps are involved: S1, putting the ball-milled silicon dioxide into a CVD rotary kiln, introducing a gaseous carbon source for vapor deposition carbon coating, and then calcining at a high temperature under an inert atmosphere to obtain a silicon-oxygen negative electrode core; S2, mixing the silicon-oxygen negative electrode core, the binder and the deionized water in step S1, stirring them evenly by heating in a water bath, and then ultrasonically dispersing them to obtain a solution containing the binder uniformly coated on the surface of the silicon-oxygen negative electrode core; S3, modifying the conductive agent with a binder to obtain a conductive agent solution with good dispersibility; S4, mixing the conductive agent solution prepared in S3 with the solution prepared in S2 to obtain a slurry containing a conductive agent and a binder to cover the surface of the silicon-oxygen negative electrode core; S5, drying, molding and fusing the slurry prepared in S4 to obtain a granular powder containing a conductive agent and a binder co-coated on the surface of the silicon-oxygen negative electrode core; S6. The material powder treated in S5 is subjected to high-temperature carbonization in an inert atmosphere to complete the coating of the surface of the silicon-oxygen negative electrode core by the artificial SEI film layer, thereby obtaining a silicon-oxygen negative electrode material containing an artificial SEI film.
3. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 2, characterized in that: In S1, the gaseous carbon source is one or more of methane, ethane, acetylene, and propylene; the inert atmosphere is one or more of nitrogen or argon, wherein the gas flow ratio of the gaseous carbon source to the inert atmosphere is 1:
2.
4. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 2, characterized in that: In S1, the temperature of vapor deposition is 800~1000 ℃, and the time of vapor deposition is 2-4 h; the temperature of high-temperature calcination is 800℃~1000℃, and the time of high-temperature calcination is 2~3 h.
5. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 2, characterized in that: In S2, the binder is one or more of sodium carboxymethyl cellulose, sodium alginate, and polyacrylic acid; The water bath heating temperature is 40~60 ℃, and the water bath heating time is 30~60 min.
6. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 2, characterized in that: In S3, the conductive agent is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, conductive carbon black, and graphene; The binder is one or more of sodium carboxymethyl cellulose, sodium alginate and polyacrylic acid.
7. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 2, characterized in that: In S4, the solid content of the slurry is 8~10%.
8. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 2, characterized in that: In S5, the drying temperature is 80~120 ℃; the fusion machine speed is 400~600 rpm, and the fusion time is 30~60 min.
9. The method for preparing a silicon-oxygen negative electrode material containing an artificial SEI film according to claim 2, characterized in that: In S6, the high-temperature carbonization temperature is 600~800 ℃, the heating rate is 5~10 ℃ / min, the high-temperature carbonization time is 2~3h, and the inert atmosphere is one or both of nitrogen and argon.
10. The use of a silicon-oxygen negative electrode material containing an artificial SEI film as claimed in claim 1, characterized in that: Silicon-oxygen negative electrode materials are used in lithium-ion batteries.
Citation Information
Patent Citations
Silicon-carbon composite material, lithium ion battery, and preparation method and application of silicon-carbon composite material
CN103633295A
Composite conductive agent slurry for silicon-carbon anode and preparation method and application thereof
CN105576248A
Surface modification method for silicon negative electrode material of lithium ion battery, silicon negative electrode material and application
CN106328913A
Silicon-based composite negative electrode material and preparation method and application thereof
CN111525110A
Carbon nanotube-connected double-carbon-layer-coated mesoporous silicon monoxide composite material as well as preparation method and application of carbon nanotube-connected double-carbon-layer-coated mesoporous silicon monoxide composite material
CN114122397A
Cited By
Preparation method of lithium manganate battery adopting graphite microchip composite positive electrode material
CN113921771A